Entrepreneurial Orientation, Market Orientation, Managerial Accounting and Manufacturing SMEs Satisfaction: Orientasi Kewirausahaan, Orientasi Pasar, Akuntansi Manajerial dan Kepuasan UKM Manufaktur - Abdulkarim Kanaan-Jebna; Ahamd Suhaimi Baharudi; Tariq Tawfeeq Yousif Alabdullah (Universitas Muhammadiyah Sidoarjo, 2022)
From a management accounting perspective, this study aims at examining the relations of entrepreneurial and market orientations and SMEs satisfaction in terms of financial and non-financial performance. SEM was conducted on 107 responses including management accountants from the manufacturing SMEs in Malaysia. The results reveal a null relationship between entrepreneurial orientation and financial-performance satisfaction, while it shows a positive impact on non-financial performance. In contrast, market orientation affects financial and non-financial performance positively. However, to understand the null impacts, interviews were conducted with owner-managers of manufacturing SMEs in Penang. Based on the interviews and the analysis, practical implications are provided to entrepreneurs of SMEs, the Malaysian government, and researchers.